A critical examination of collusion, the pricing behaviour of a multi-product cartel and the cartel enforcement record in South Africa - Muzata, Tapera Gilbert (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.